Isolation and Characterization of Madariaga Virus from a Horse in Paraiba State, Brazil - Silva, M. L. C. R.; Auguste, A. J.; Terzian, A. C. B.; Vedovello, D.; Riet-Correa, F.; Macario, V. M. K.; Mourao, M. P. G.; Ullmann, L. S. [UNESP]; Araujo, J. P. [UNESP]; Weaver, S. C.; Nogueira, M. L. (Wiley-Blackwell, 2017)
Madariaga virus (MADV), the new species designation for the South American isolates of eastern equine encephalitis virus (EEEV), is genetically divergent and substantially different in ecology and pathogenesis from North American EEEV strains. We isolated and characterized a MADV isolate obtained from a horse in Brazil. Our results support previous phylogenetic studies showing there are three genetically distinct MADV lineages. The MADV isolate from Paraiba State belongs to the South American lineage III and is closely related to Peruvian, Colombian and Venezuelan isolates.
Keywords: arboviruses; Alphavirus; horse; eastern equine encephalitis virus; Madariaga virus